Osteoclast visualization: Tartrate-resistant acid phosphatase activity staining using NewFuchsin compatible with non-aqueous mounting and tissue clearing - Takashi Nakamura; Katsuhiro Kawaai; Yukiko Kuroda; Koichi Matsuo (MethodsX, 2025)
Tartrate-resistant acid phosphatase (TRAP) staining is widely used to stain osteoclasts in histological bone sections. The red dye formed by the conventional TRAP enzymatic reaction using naphthol AS-MX (or AS-BI) phosphate and fast red-violet (or garnet) chromogens is readily soluble in alcohol or xylene and requires air-drying prior to cover slipping or the use of an aqueous mounting medium. However, the use of an aqueous mounting medium makes it difficult to store stained specimens for a long time. In this modified method, a new fuchsin (NewFuchsin) was used as a chromogen, which enabled dehydration and clearing after staining and the use of a non-aqueous organic solvent-based mounting medium. Samples prepared using this modified TRAP activity staining method (NewFuchsin TRAP staining) have the following advantages over conventional TRAP staining: • The staining of sections provides a clear histological image and allows for long-term preservation. • The red dye formed by NewFuchsin TRAP staining can be detected not only in the bright field, but also in the fluorescent field. • Combined with tissue clearing using ethyl cinnamate, osteoclasts are observed using three-dimensional imaging.